A Comprehensive Review on Microbial Bioremediation of Industrial Dye - Dey, Sreedeep; Mandal, Barnali (RADINKA JAYA UTAMA PUBLISHER, 2025)
Synthetic dyes, widely utilized across industries such as textiles, cosmetics, and pharmaceuticals, represent a significant environmental hazard due to their persistence, toxicity, and resistance to conventional treatment methods. Current remediation strategies, including coagulation, adsorption, and advanced oxidation processes, are limited by high energy demands, secondary pollutant generation, and inefficiency in degrading recalcitrant dye structures. This review comprehensively evaluates microbial dye remediation as a sustainable alternative, emphasizing the enzymatic potential of bacteria, fungi, algae, and yeasts. Critical findings underscore the efficacy of microbial enzymes, including laccases, azoreductases, and peroxidases, in degrading complex dyes such as azo and anthraquinone derivatives into less toxic or mineralized products. Microbial consortia demonstrate enhanced degradation through metabolic complementarity, while innovative bioreactor systems, such as microbial fuel cells and membrane bioreactors, achieve improved efficiency and energy recovery. Despite these advances, challenges such as the production of toxic intermediates (e.g., aromatic amines), microbial sensitivity to environmental fluctuations, and sludge generation remain obstacles to industrial-scale application. The review highlights the potential of integrating microbial systems with nanotechnology and advanced oxidation processes to address these limitations. Genetic engineering and synthetic biology are proposed as critical tools for enhancing microbial resilience and enzymatic specificity. Future research should focus on hybrid remediation approaches, real-time environmental monitoring, and the development of standardized, scalable protocols. By synthesizing advancements in microbial biotechnology and wastewater management, this review provides a strategic framework for addressing industrial dye pollution, aligning with global sustainability goals and advancing the field of bioremediation.